PSYCHOLOGICAL FEATURES OF THE PSYCHOLOGIST'S PERSONALITY IN THE PARADIGMS OF THE EXISTING CLASSIFICATIONS OF OCCUPATIONS - Vlasenko, Andrii (PSYCHOLOGICAL JOURNAL, 2018)
The article presents a detailed analysis of social trends, which determine the significance of studying psychologist’s personal features. Analysis of the relevant Ukrainian and foreign scientific literature allowed the author to identify the most applicable psychological classifications of occupations. The author discusses the place of the profession of a psychologist in J. L. Holland classification of occupations as the most popular Western occupational classification and in E. Klimov four-level classification of occupations as the most popular psychological occupational classification among Ukrainian psychologists and managers. The author analyzes some aspects of these classifications from the theoretical and practical perspectives. Based on the place of the profession of a psychologist in these classifications, the article explores the main psychological characteristics of the profession of a psychologist paying special attention to some important aspects and differences in the definitions of this profession in various occupational classifications as well as different hierarchies of the main psychological characteristics of the profession of a psychologist.J. Holland and E. Klimov classifications distinguish quite similar psychological attributes of the individual to make a good psychologist, which include, among others, good communicative skills, empathy and tolerance. The author also analyzes the leading research trends in studying the profession of a psychologist and makes conclusions about the increased role of psychologists in today’s difficult social and economic situation in Ukraine, researcher’s close attention to this profession as well as individual’s profession-relevant psychological features. The author describes the place of the profession of a psychologist in different foreign and Ukrainian occupational classifications and discusses the main psychologist’s profession-critical attributes. The author also makes conclusions about the increased role of psychologists in today’s difficult social and economic situation in Ukraine.